Assessing The Impact of Rising Cost of Materials On Construction Activities in Enugu, Enugu State, Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2024)
This study focused on assessing the impact of rising cost of building materials on construction activities in Enugu, Enugu state, Nigeria. The aim of this study is to assess the impact of rising cost of materials on construction activities in Enugu, Nigeria in order to proffer a solution to the rise in the cost of these materials used in everyday construction in Enugu state. With the following objectives; to identify the factors that lead to increasing cost of material in Enugu State, Nigeria; to assess the impact of rising cost of materials on construction activities in Enugu; to proffer solutions to the rise in the cost of building materials. The research design employed was primary and secondary which encompasses descriptions and quantitative analysis on a randomly selected sample of receipt of building materials from the suppliers over the years. The population of the study is 223 professionals in the field and sample size of 143 which was gotten using Taro Yamane formula. The findings of the study reveals that the factors that lead to increasing cost on the building construction activities in Enugu State are; fluctuations in material costs, design changes and scope creep, regulatory compliance and permitting, project delays, weather and environmental factors, technology and innovation costs, interest rates and financing costs, and others. Finally, the study recommends that there will be need for relevant authorities in the building industry to re-examine and educate the people on its existence and equally generate the possible ways of reducing the increasing cost of building materials so as to enhance the building construction industry in Nigeria.